“Procesamiento de cuerito de cerdo por expandido” - Chávez Pinchi,Miguel (2000)
The current research work was carried out in the laboratories of the Agroindustrial Engineering Faculty of the National University of San Martín. It was done in three stages: first stage, benefit and obtainance of the pig skin as raw material; second, elaboration ofthe ''Expanded pig skin"; and third, Evaluation ofthe appropriate package for the storage of the expanded pig skin for 90 days long, and therefore evaluating physical-chemical, organoleptic and microbiological behavior of the product under two temperature conditions of28ºC and 37ºC. It was used the skin of a 6 months old LANDRACE race pig, obtaining the eviscerated pig with weight of 62,5 Kg, with 11,50 Kg of skin wich represents 18.4% ofthe eviscerated pig, head 6,4%, feet 1,6%, bones 14,4%, rubish 9,6%. A visual inspection was carried out to the pig skin for to determínate the presence of hair, and the it was cutted into slices of 20 cm long and 1 O cm wide for to make easier the coming operations as the fat take out. The fat take out was done one by hand without scalding and another scalding, and the results showed up that hand made whit scalding fat take out was the best. The lean skin was salted in humid pile along 30 minutes with a concentration of 7ºBe. Immediatelly it was dried with a forced ventilation drier at 50ºC of temperature for 15 hours 15 minutes, where it was obtained a final humidity of 7 ,25%, a parameter that is necessary for to be able to pass to the next process. The dried product was expanded by fryring in pork's fat in a 3: 1 relation, whit a temperature of 185 ºC, for along 2 minutes. The obtained product (Expanded pig skin) was defined as a crispy and salted product with a high protein level (70,15%), which has the following flow diagram: cutting, fat taking out, salting, drying and expanding by fry. The expanded pig skin was stored for 90 days period under two different temperature conditions, 28ºC and 37ºC, using 3 kinds of packings: Aluminum bilaminated, Polyethylene and Cellophane of high density in both cases. In this stage the shelf-life behavior was evaluated every 15 days by testing its physical-chemical properties 11 (humidity, iodine index, acidity index, peroxide index), and a sensorial evaluation every 30 days whit the purpose of determinate the appropiate packing for a 90 days lingering storage. The appropriate packing for the 90 days storage was the aluminum bilaminated, because there is no significative variations in its physical-chemical properties nor in its organolepticals characteristic.